SPS432 - Fundamental Practices of Sports Psychology / Faculty of Sports Science & Recreation - UiTM, Faculty of Sport Science and Recreation (Universiti Teknologi MARA (UiTM), 2024)
This course will cover various psychological principles associated with the sport. This course is designed to assist the student in examining how psychological variables influence participation patterns in sport and how participation in sport can affect the psychological characteristic of an individual. Class content will also illustrate numerous psychological techniques that can enhance sports performance. Among the topics to be examined are the definition of psychology and sports psychology, personality and athletes, motivation, sports team, leadership, anxiety and stress in sport.